2016
DOI: 10.1160/th16-03-0223
|View full text |Cite
|
Sign up to set email alerts
|

Missense mutations in the gene encoding prothrombin corresponding to Arg596 cause antithrombin resistance and thrombomodulin resistance

Abstract: Antithrombin (AT) and thrombomodulin (TM) play important roles in the process of natural anticoagulation in vivo. Recently, we reported that the prothrombin Yukuhashi mutation (p.Arg596Leu) was associated with AT and TM resistance-related thrombophilia. To assess the AT and TM resistances associated with other missense mutations by single base substitution in the Arg596 codon, we generated recombinant variants (596Gln, 596Trp, 596Gly, and 596Pro) and investigated the effects on AT and TM anticoagulant function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 29 publications
0
15
0
1
Order By: Relevance
“…Antithrombin‐resistant prothrombin is a mutant presenting paradoxical features in thrombosis and haemostasis in vivo, that is the mutant thrombin derived from antithrombin‐resistant prothrombin displays a mild decline in the procoagulant activity. However, a substantial impairment in its inactivation by antithrombin results in a prolongation of the procoagulant activity, causing thromboembolism in some patients . In clinical laboratory tests, plasma from the patient with a heterozygous ATR mutation does not exhibit a significant alteration in PT and APTT levels .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antithrombin‐resistant prothrombin is a mutant presenting paradoxical features in thrombosis and haemostasis in vivo, that is the mutant thrombin derived from antithrombin‐resistant prothrombin displays a mild decline in the procoagulant activity. However, a substantial impairment in its inactivation by antithrombin results in a prolongation of the procoagulant activity, causing thromboembolism in some patients . In clinical laboratory tests, plasma from the patient with a heterozygous ATR mutation does not exhibit a significant alteration in PT and APTT levels .…”
Section: Discussionmentioning
confidence: 99%
“…However, a substantial impairment in its inactivation by antithrombin results in a prolongation of the procoagulant activity, causing thromboembolism in some patients. 10,12,15,17 In clinical laboratory tests, plasma from the patient with a heterozygous ATR mutation does not exhibit a significant alteration in PT and APTT levels. 12,15 Miljic et al reported a significant decline in the PT-based prothrombin activity and an increase in the endogenous thrombin potential (ETP) in the thrombin generation assay in heterozygous carriers of prothrombin Belgrade.…”
Section: Discussionmentioning
confidence: 99%
“…The most common of them are (Fig. 8): proteins C and S deficiency; antithrombin III deficiency; anomaly of coagulation factor V (the Leiden mutation); anomaly of prothrombin G 202110A [12]. These congenital disorders lead to disruption of the blood coagulation system.…”
Section: Venous Stasismentioning
confidence: 99%
“…7 For example, it was reported recently that missense mutations in the gene encoding prothrombin corresponding to Arg596 cause antithrombin resistance and thrombomodulin resistance-related thrombophilia. 8 Other genetic risk factors for VTE are dysfibrinogenemia ( FGG , fibrinogen γ′), 11 F11 gene, 9 and non-O blood group. 12 –14 The initial observation that an elevated factor VIII level is a risk factor for venous thrombosis 15 is now supported by robust evidence.…”
Section: Inherited Thrombophiliamentioning
confidence: 99%